2006
DOI: 10.1016/j.pbb.2006.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Morphine analgesic tolerance in 129P3/J and 129S6/SvEv mice

Abstract: Morphine analgesic tolerance is heritable in both humans and rodents, with some individuals and strains exhibiting little and others exhibiting robust tolerance. 129S6/SvEv and 129P3/J mice reportedly do not demonstrate tolerance to morphine analgesia. Using our laboratory's standard morphine tolerance regimen and a between-subjects design, tolerance developed in the hot plate and tail withdrawal assays as indicated by a change in analgesic efficacy following a morphine challenge dose. Furthermore, the non-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Baseline hot plate latency was analyzed via two-way ANOVA (Sex, Genotype) followed by post-hoc Welch's t-test to identify the effect of Genotype. We measured fentanyl analgesia using Percent Maximum Possible Effect (%MPE; Bryant et al 2006). We analyzed FENT analgesia via three-way ANOVA (Sex, Genotype, Dose), followed by a post-hoc two-way ANOVA with Genotype and Dose as factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline hot plate latency was analyzed via two-way ANOVA (Sex, Genotype) followed by post-hoc Welch's t-test to identify the effect of Genotype. We measured fentanyl analgesia using Percent Maximum Possible Effect (%MPE; Bryant et al 2006). We analyzed FENT analgesia via three-way ANOVA (Sex, Genotype, Dose), followed by a post-hoc two-way ANOVA with Genotype and Dose as factors.…”
Section: Discussionmentioning
confidence: 99%
“…We measured fentanyl analgesia using Percent Maximum Possible Effect (%MPE) (Bryant et al ., 2006). We analyzed FENT analgesia via three-way ANOVA (Sex, Genotype, Dose), followed by a post-hoc two-way ANOVA with Genotype and Dose as factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of morphine analgesic tolerance utilizing wild-type inbred strains have shown substantial shifts to the right in the dose-response curve of Balb/c, CBA, and C57BL/6 mice, however, there is no change in analgesic efficacy at lower morphine doses (< 10 mg/kg) for C57BL/6 and CBA mice (Bryant et al, 2006; Kest et al, 2002a; Liang et al, 2006a). In the current study, by using a single morphine challenge dose (7.5 mg/kg), only wild-type Balb/c mice exhibited analgesic tolerance, but not CBA and C57BL/6 mice, which supports previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Organismic effects on morphine tolerance-Antinociceptive tolerance was observed following cumulative intracranial microinjections of morphine into the PAG in the rat (795). Morphine analgesic tolerance in 129P3/J and 129S6/SvEv mice was largely absent because of differences in tail-flick responsivity between these strains and C57BL/6J mice (148). Acute morphine tolerance was observed in proestrous, but not ovariectomized female rats; chronic estradiol in ovariectomized animals reinstated acute morphine tolerance.…”
Section: A Animal Models In Tolerancementioning
confidence: 99%